The Effect of Governance and Member Participation on Households’ Consumption and Welfare: a Case Study of The Women Cooperatives (KOPWAN) in The City of Kediri - Nekky Rahmiyati; Sri Andayani; Endang Indartuti (Enrichment : Journal of Management, 2020)
This study attempts to find the effect of governance and member participation on households’ consumption and welfare, a study in KOPWAN I the city of Kediri. The analysis uses Structural Equation Model (SEM) based on Partial Least Square (PLS). The sample of 493 respondent were drawn from the KOPWAN members; using purposive sampling method. The result shows the significant effect of co-op governance on member participation; member participation significantly affects households’ economic growth and households’ economic growth in turn increase their welfare.